The Nrf2 Activator Vinylsulfone Reduces High Glucose-Induced Neural Tube Defects by Suppressing Cellular Stress and Apoptosis. (August 2016) - Dong, Daoyin; Reece, E. Albert; Yang, Peixin
The nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway is one of the primary pathways responsible for the cellular defense system against oxidative stress. Oxidative stress-induced apoptosis is a causal event in diabetic embryopathy. Thus, the Nrf2 pathway may play an important role in the induction of diabetic embryopathy. In the present study, we investigated the potentially protective effect of the Nrf2 activator, vinylsulfone, on high glucose-induced cellular stress, apoptosis, and neural tube defects (NTDs). Embryonic day 8.5 (E8.5) whole mouse embryos were cultured in normal (5 mmol/L) or high (16.7 mmol/L) glucose conditions, with or without vinylsulfone. At a concentration of 10 μmol/L, vinylsulfone had an inhibitory effect on high glucose-induced NTD formation, but it was not significant. At a concentration of 20 μmol/L, vinylsulfone significantly reduced high glucose-induced NTDs. In addition, 20 μmol/L vinylsulfone abrogated the high glucose-induced oxidative stress markers lipid hydroperoxide (LPO), 4-hydroxynonenal (4-HNE), and nitrotyrosine-modified proteins. The high glucose-induced endoplasmic reticulum (ER) stress biomarkers were also suppressed by 20 μmol/L vinylsulfone through the inhibition of phosphorylated protein kinase RNA-like ER kinase (PERK), inositol requiring protein 1α (IRE1a), eukaryotic initiation factor 2α (eIF2a), upregulated C/EBP-homologous protein (CHOP), binding immunoglobulin protein (BiP), and x-box binding protein 1 (XBP1) messenger RNA splicing. Furthermore, 20 μmol/L vinylsulfone abolished caspase 3 and caspase 8 cleavage, markers of apoptosis, in embryos cultured under high glucose conditions. The Nrf2 activator, vinylsulfone, is protective against high glucose-induced cellular stress, caspase activation, and subsequent NTD formation. Our data suggest that vinylsulfone supplementation is a potential therapy for diabetes-associated neurodevelopmental defects.